Artificial intelligence and machine learning in healthcare: Transforming clinical practice and addressing challenges (Panacea Journal of Medical Sciences, 2024)
Artificial Intelligence (AI) and Machine Learning (ML) arerevolutionizing healthcare by improving patient outcomes,enhancing diagnostics, and optimizing clinical workflows.AI-powered systems are increasingly being adopted toassist in diagnostics, personalized medicine, radiology,and predictive analytics, offering improved accuracy andefficiency in clinical decision-making. 1 However, theseadvancements also pose significant ethical, regulatory, andbias-related concerns that require careful consideration toensure equitable and safe implementation.